Assessing the vulnerability of military theater distribution routes - Muckensturm, Joshua R.; Longhorn, Dave C. (Journal of Defense Analytics and Logistics, 2019)
PurposeThis paper introduces a new heuristic algorithm that aims to solve the military route vulnerability problem, which involves assessing the vulnerability of military cargo flowing over roads and railways subject to enemy interdiction.Design/methodology/approachGraph theory, a heuristic and a binary integer program are used in this paper.FindingsThis work allows transportation analysts at the United States Transportation Command to identify a relatively small number of roads or railways that, if interdicted by an enemy, could disrupt the flow of military cargo within any theater of operation.Research limitations/implicationsThis research does not capture aspects of time, such as the reality that cargo requirements and enemy threats may fluctuate each day of the contingency.Practical implicationsThis work provides military logistics planners and decision-makers with a vulnerability assessment of theater distribution routes, including insights into which specific roads and railways may require protection to ensure the successful delivery of cargo from ports of debarkation to final destinations.Originality/valueThis work merges network connectivity and flow characteristics with enemy threat assessments to identify militarily-useful roads and railways most vulnerable to enemy interdictions. A geographic combatant command recently used this specific research approach to support their request for rapid rail repair capability.